2003
DOI: 10.1124/jpet.103.055319
|View full text |Cite
|
Sign up to set email alerts
|

The Competitive N-Methyl-d-aspartate Receptor Antagonist (-)-6-Phosphonomethyl-deca-hydroisoquinoline-3-carboxylic Acid (LY235959) Potentiates the Antinociceptive Effects of Opioids That Vary in Efficacy at the μ-Opioid Receptor

Abstract: ABSTRACT(Ϫ)-6-Phosphonomethyl-deca-hydroisoquinoline-3-carboxylic acid (LY235959) is a competitive N-methyl-D-aspartate receptor antagonist shown to prevent the development of tolerance to the antinociceptive effects of morphine in rodents. Although administration of LY235959 alone generally does not produce antinociception, LY235959 potentiates the antinociceptive effects of morphine in squirrel monkeys. The present study was designed to determine whether LY235959 would potentiate the acute antinociceptive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In agreement with these findings, LY235959 produced a synergistic interaction with each of the opioids, regardless of efficacy, in the assay of thermal nociception. These findings agree with data obtained in squirrel monkeys (Allen et al, 2003), suggesting efficacy is not an important determinant of interactions between NMDA and opioid receptors on the endpoint of antincoception.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with these findings, LY235959 produced a synergistic interaction with each of the opioids, regardless of efficacy, in the assay of thermal nociception. These findings agree with data obtained in squirrel monkeys (Allen et al, 2003), suggesting efficacy is not an important determinant of interactions between NMDA and opioid receptors on the endpoint of antincoception.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has demonstrated that NMDA antagonists can increase the antinociceptive effects of morphine (Allen and Dykstra, 2003;Nemmani et al, 2004;Fischer et al, 2005;Grisel et al, 2005). Although the interactive effects of morphine and NMDA receptor antagonists have been investigated in various antinociceptive measures, the first purpose of the current study was to assess these interactions using a formally quantitative approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buprenorphine and meperidine paired with naltrexone occasioned little or no responding on the MOR 3 NTX-appropriate lever, even at doses that were behaviorally active and were well within the range of doses shown to be effective in other behavioral models using squirrel monkeys (Schaefer and Holtzman, 1977;Dykstra, 1983Dykstra, , 1985DeRossett and Holtzman, 1984;Negus et al, 1991;Dykstra et al, 2002;Allen et al, 2003). Likewise, pretreatment with the partial -opioid receptor agonist nalbuphine in combination with 0.1 mg/kg naltrexone failed to elicit criterion levels of responding, even at a dose 10 times higher than that of the training dose of morphine.…”
Section: Discussionmentioning
confidence: 98%